Penyuluhan terhadap Efektivitas Mc Kenzie Exerciseuntuk Mengurangi Keluhan Low Back Pain pada Kelompok Bola Tarkam Kota Malang - Dimas Satria Pujasera; Safun Rahmanto (Rena Cipta Mandiri, 2025)
Low Back Pain (LBP) is a musculoskeletal disorder resulting from improper ergonomics. Low back pain is a highly prevalent global health issue that leads to activity limitations and work absenteeism. One occupation with a high ergonomic risk is office work involving the use of computers or laptops. Among office workers at Mining Company X, 96.4% were found to have a moderate ergonomic risk and were classified as requiring corrective action based on the Rapid Entire Body Assessment (REBA) method. In addition, these office workers reported moderate severity of low back pain complaints. The purpose of this study was to determine the relationship between working posture and low back pain complaints among office workers at Mining Company X. This study employed an observational design with a cross-sectional approach. The respondents consisted of all office workers at Mining Company X, totaling 30 participants. Data analysis was conducted using descriptive analysis for each variable through frequency distribution tables, as well as cross-tabulation and contingency correlation tests to assess the strength of the relationship between variables. The results showed that the majority of workers had hazardous working postures (67%) and experienced moderate low back pain complaints (67%). There was a moderately strong relationship between working posture and low back pain (C = 0.482). It can be concluded that there is a relationship between working posture and low back pain among office workers at Mining Company X.